1997
DOI: 10.1021/jo962197c
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of Pentacarbonyl(1-acyloxyalkylidene)chromium(0) Complexes:  Formation of Z-Enol Esters

Abstract: Pentacarbonyl(1-acyloxyalkylidene)chromium(0) complexes, formed in situ by reaction of the corresponding tetramethylammonium pentacarbonyl(1-oxoalkyl)chromate(1−) salts with carboxylic acid halides, affords enol esters in moderate to good yields. In all cases examined, the Z-enol ester was obtained as the major or exclusive isomer. Addition of 1 equiv of pyridine to the reaction mixture substantially improved the Z/E ratio and, in most cases, increased the chemical yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Bruneau reported that ruthenium-catalyzed addition of carboxylates to terminal alkynes can afford ( Z )-alk-1-en-yl esters including conjugated dienyl esters 3b. However, to the best of our knowledge, the general method for the stereodefined preparation of ( Z , E )- or ( Z , Z )-conjugated alkadienyl carboxylates has not been reported, perhaps becuase of its thermodynamic instability. 1d, So, it seems important to develop an effective method for the construction of ( Z , E )- or ( Z , Z )-conjugated alkadienyl carboxylates. In this communication, we wish to report a novel approach to ( Z , E )- or ( Z , Z )-conjugated alkadienyl carboxylates.…”
mentioning
confidence: 99%
“…Bruneau reported that ruthenium-catalyzed addition of carboxylates to terminal alkynes can afford ( Z )-alk-1-en-yl esters including conjugated dienyl esters 3b. However, to the best of our knowledge, the general method for the stereodefined preparation of ( Z , E )- or ( Z , Z )-conjugated alkadienyl carboxylates has not been reported, perhaps becuase of its thermodynamic instability. 1d, So, it seems important to develop an effective method for the construction of ( Z , E )- or ( Z , Z )-conjugated alkadienyl carboxylates. In this communication, we wish to report a novel approach to ( Z , E )- or ( Z , Z )-conjugated alkadienyl carboxylates.…”
mentioning
confidence: 99%
“…The present method using sulfonium salts has the following advantages: (1) While a longer reaction time (12 h) is needed than that in the known method 12 using oxonium salts 6 , a variety of functionalized alkyl groups with a secondary carbon can be effectively introduced. (2) This reaction can be carried out at room temperature, although the known method using acyloxy intermediate 8 gives enol esters at room temperature when α-hydrogens next to the carbene carbon atom are present . (3) The present method is particularly useful for preparing carbene complexes 18 with a hydroxyl group, since the known method via acyloxy intermediate 8 gives a mixture of 18 and a biscarbene complex like 20 .…”
Section: Resultsmentioning
confidence: 97%
“…However, this method is limited to the preparation of alkoxycarbene complexes containing simple methoxy and ethoxy groups. The preparation of Fischer-type carbene complexes containing functionalized alkyl groups has been reported (Scheme ). 6a,10a,, However, the methods used to prepare alkoxy carbene complexes of chromium, molybdenum, and tungsten are still limited. ,
3
…”
Section: Introductionmentioning
confidence: 99%